Aptamer-based applications for cardiovascular disease - Chen, Xinyuan; Ma, Yue; Xie, Yuquan; Pu, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Cardiovascular disease (especially atherosclerosis) is a major cause of death worldwide. Recently, aptamers are single-stranded oligonucleotides selected from a random sequence pool, with the ability to form three-dimensional structures that bind to target molecules with superior specificity. Their physicochemical properties enable them to rival antibodies in cardiac applications. Their commodious synthesis, with the ability for site-specific modifications for functional moieties, make aptamers excellent recognition motifs for cardiac biomarker discovery and detection. Moreover, aptamers can be selected or engineered to aim clinical drug design, especially in anti-thrombosis therapy. Von Willebrand Factor plays a unique role in the formation of thrombus, and as an aptamer targeting molecule, has shown initial success in antithrombotic treatment. A combination of vWF and nucleic acid aptamers can effectively inhibit the progression of blood clots, presenting a positive diagnosis and therapeutic effect, as well as laying a novel theory and strategy to improve biocompatibility paclitaxel drug balloon or implanted stent in the future. This review summarizes aptamer-based applications in cardiovascular disease, including biomarker discovery and future management strategy. Although relevant applications are relatively new, the significant advancements achieved have demonstrated that aptamers can be promising agents to realize the integration of diagnosis and therapy in cardiac research.